2017
DOI: 10.1111/inr.12358
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of treatment satisfaction and well‐being among patients with type II diabetes

Abstract: These findings are important in assisting nurses and other healthcare professionals in identifying patients with diabetes with low treatment satisfaction who may present a greater risk for poor well-being. Additionally, they lend support to developing policies for frequent screenings and special therapeutic interventions that are needed to maximize patients' treatment satisfaction and well-being in the Middle East and elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
(44 reference statements)
0
12
1
Order By: Relevance
“…Our group performed a previous study in people with type 2 diabetes and found an association of greater TS with higher adherence to the MedDiet [10]. Two cross-sectional studies performed in people with type 2 diabetes only found a positive relationship between TS and the adherence to medical nutrition therapy [13,14]; however, despite observing a relationship between aHEI and some items of TS in this study, we did not find any association between the dietary pattern and the overall TS. This could be due to the small number of participants included in our study with a poorer TS final score.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our group performed a previous study in people with type 2 diabetes and found an association of greater TS with higher adherence to the MedDiet [10]. Two cross-sectional studies performed in people with type 2 diabetes only found a positive relationship between TS and the adherence to medical nutrition therapy [13,14]; however, despite observing a relationship between aHEI and some items of TS in this study, we did not find any association between the dietary pattern and the overall TS. This could be due to the small number of participants included in our study with a poorer TS final score.…”
Section: Discussioncontrasting
confidence: 84%
“…On the other hand, another study performed in people with diabetes (without identifying the type of diabetes) found a higher health-related quality of life (HRQoL) associated with the combination of multiple healthy lifestyle habits (no smoking, regular physical activity, and a higher intake of fruits and vegetables) [12]. Other cross-sectional studies have only assessed the relationship between TS and adherence to medical nutrition therapy in people with type 2 diabetes [13,14]; they found a higher TS in those who showed a higher adherence to the nutritional recommendations. In adults with T1D, no studies have been designed to assess the potential impact of dietary pattern on QoL and TS.…”
Section: Introductionmentioning
confidence: 99%
“…Our group discussions revealed the elements of value creation with focus on chronic diseases management. In modern management, value creation is a paradigm involving multiple stakeholders in the marketing process, who work together at various points of the consumption process to create value for patients 26 . It is viewed as a process in which organizations and consumers interact at various stages of consumption to create the service 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The Malaysian study involved 197 T2DM patients from primary health facilities and reported that patient education level, number of oral antidiabetic medication taken, and type of insulin regime used affected the interaction outcome between a patient with T2DM and a physician 46 . In Jordan, the descriptive correlational study (n = 1002) found that perception about T2DM treatment was worse among women than men, and heart disease as a comorbidity with diabetes was also a significant indicator for low treatment satisfaction 47 . The researchers identified the phases of T2DM progression: Prior to any Diagnosis, Pre -diabetic (diagnosed), Onset of T2DM, Health Maintenance and Prevention, Complications-Minor or Major 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation